2016
DOI: 10.1111/ggi.12893
|View full text |Cite
|
Sign up to set email alerts
|

Mobility, balance and frailty in community‐dwelling older adults: What is the best 1‐year predictor of falls?

Abstract: The findings showed that the TFI might be an effective tool for predicting falls at 12 months in aged populations, probably because it is able to capture the multifactorial facets that can lead to falls. Geriatr Gerontol Int 2017; 17: 1463-1469.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
0
30
0
2
Order By: Relevance
“…17 In a sample of 963 Brazilian people, aged 60 years and older, the TFI predicted both hospitalization and falls. 35 Mulasso et al showed that the physical and psychological domains of the TFI were significant predictors of falls among 192 communitydwelling older people; 36 the TFI was a stronger predictor of falls when compared with the One Leg Standing (OLS) test 37 and the Timed Up and Go (TUG) test. 38 The predictive validity of total frailty and physical frailty for disability, healthcare utilization, and falls was also confirmed by the AUCs.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a sample of 963 Brazilian people, aged 60 years and older, the TFI predicted both hospitalization and falls. 35 Mulasso et al showed that the physical and psychological domains of the TFI were significant predictors of falls among 192 communitydwelling older people; 36 the TFI was a stronger predictor of falls when compared with the One Leg Standing (OLS) test 37 and the Timed Up and Go (TUG) test. 38 The predictive validity of total frailty and physical frailty for disability, healthcare utilization, and falls was also confirmed by the AUCs.…”
Section: Discussionmentioning
confidence: 99%
“…Falls are a major public health concern for the older adult population . Several epidemiological studies have identified medical risk factors for falling among older adults, such as age, depression, polypharmacy, sleeping medications, and hypotension .…”
Section: Introductionmentioning
confidence: 99%
“…F alls are a major public health concern for the older adult population. [1][2][3] Several epidemiological studies have identified medical risk factors for falling among older adults, such as age, depression, polypharmacy, sleeping medications, and hypotension. 4,5 However, the prevention of falls among the elderly is complex, 5 and potential dietary determinants are only poorly identified.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recent data indicate that performing multidimensional assessment using the TFI gives predictive information about falls in the next year. 18 Similarly, several recent studies indicated that several indices of frailty were closely related with 12-month all-cause mortality after transcatheter aortic valve implantation. 19,20 However, a multidimensional tool such as the TFI was not used in these studies.…”
Section: Discussionmentioning
confidence: 91%